Accuracy of Computer-Guided Template-Based Implant Surgery: A Computed Tomography–Based Clinical Follow-Up Study. Issue 6 (December 2019) - Schelbert, Tobias; Gander, Thomas; Blumer, Michael; Jung, Ronald; Rücker, Martin; Rostetter, Claudio
Abstract : Objective: The aim of this clinical study was to analyze the accuracy of computer-guided implant surgery. Materials and Methods: Assisted by computed tomography (CT)-based planning software and navigational templates, 16 patients successfully received 26 dental implants. Each implant parameter (a–d) was calculated based on superimposed preoperative and postoperative cone beam CT scans: (a) deviation at entry point; (b) deviation at apex; (c) angular deviation; and (d) depth deviation. Results: Mean central deviation at implant entry point and apex was 0.91 mm (standard error [SE] = 0.11 mm; 95% confidence interval [CI]: 0.69–1.13) and 1.22 mm (SE = 0.11 mm; 95% CI: 0.99–1.45), respectively. Mean angulation deviation was 4.11 degrees (SE = 0.52 degrees; 95% CI: 3.04–5.17) and the average depth deviation was 0.65 mm (SE = 0.11 mm; 95% CI: 0.42–0.87). For the total number of implants placed, the maximum error was 2.34 mm at entry point, 2.71 mm at apex, 9.44 degrees in angular deviation, and 2.00 mm in depth deviation. Conclusion: Great accuracy was reached even in advanced cases with prior bone augmentation and complex traumas. This leads to the conclusion that particularly in advanced cases, computer-guided implantation can be beneficial.